DEIXIS IN TRUMP’S FINAL REMARKS AS PRESIDENT - Zakir Hossen Shaikh; Desmalia Purba; Mihir Ranjan Nayak (JURNAL DARMA AGUNG, 2023)
This study deals with Deixis, a Greek word which means pointing by language. This study aims at finding the types of Deixis used in Trump’s final remarks as president, and finding the types of Deixis most dominantly used in Trump’s final remarks as president. Descriptive qualitative design was applied in this research. Having analyzed the data, the findings of this study are: (a)There are three kinds of deixis found in Trump’s final remarks as president, they are person deixis, time deixis and place deixis; (b) Person deixis is the most dominantly used in Trump’s final remarks as president; 86.86%. The writer suggests that the students should learn Deixis as clear as possible because it is the most fundamental thing that should be mastered and the teacher or instructor of English language can teach the students about Deixis by using many written forms, such as songs’ lyrics, poems, novels, drama’s scripts and others.